2017
DOI: 10.3390/s17040677
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Sensor for Defending against Clock Glitching Attacks on the I2C Protocol in Robotic Applications

Abstract: This paper presents a study about hardware attacking and clock signal vulnerability. It considers a particular type of attack on the clock signal in the I2C protocol, and proposes the design of a new sensor for detecting and defending against this type of perturbation. The analysis of the attack and the defense is validated by means of a configurable experimental platform that emulates a differential drive robot. A set of experimental results confirm the interest of the studied vulnerabilities and the efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…For our experiment, the sensor board was connected to an Arduino ® MKR FOX 1200 board using the I2 C communication interface [28]. Figure 8 shows the wiring diagram of the sensor, which was powered up through the Arduino ® 3.3 Volt output pin (Vcc).…”
Section: Application: Thermal Analysis Of Memsmentioning
confidence: 99%
“…For our experiment, the sensor board was connected to an Arduino ® MKR FOX 1200 board using the I2 C communication interface [28]. Figure 8 shows the wiring diagram of the sensor, which was powered up through the Arduino ® 3.3 Volt output pin (Vcc).…”
Section: Application: Thermal Analysis Of Memsmentioning
confidence: 99%
“…In a later work, Timmers et al [54] showed that in an embedded Linux Operating System (OS) the privileges can be escalated from user to system privileges by performing VFI. By performing VFI against AMD's Secure Processor (SP), Buhren et al [11] where able to control the key management and by this, compromise the security of AMD's Secure Encrypted Virtualization (SEV [4,5,32,38,39,48] and Hardware Level Countermeasuress (HLCs) [10,17,19,22,30,31,50,61]. Due to the higher abstraction of ILCs, these protect against a certain Fault Model, whereas the HLCs are generally deployed to protect against a certain type of FI.…”
Section: Related Workmentioning
confidence: 99%
“…We choose this accelerometer because it has a resolution of 0.061 mg/ Least Significant Bit (LSB) in the measuring range of ±2 g and an operating range from −40 to +85 °C. This sensor was connected to an Arduino ® Nano board using the I2C communication interface [ 23 ] and the wiring diagram is reported in Figure 1 . Due to a difference in operating voltage between the IMU and the Arduino ® , a bi-directional logic converter was used.…”
Section: The Low-cost Mems Imumentioning
confidence: 99%